Strategic Communication Futures: Paradigm and Practice in a Polycrisis World - Keyan Tomaselli; Addamms Mututa (Communicare)
This article responds to Nina Overton-de Klerk’s intervention that offers a critical and transdisciplinary overview of the current state of the discipline of strategic communication, and of its future potentials. Our critical engagement originates within the context of Overton-de Klerk’s intervention, published in the contemporary conjuncture of polycrisis. Our self-reflexive study examines the significance of the discipline in relation to the social and political economic concerns of the broader cultural and media studies paradigm. The interlinkages between these fields/disciplines are examined in interdisciplinary nodal relations rather than as separated modular conceptual units. The issue of disciplinary identity is then discussed within the contemporary South African research context. A key argument is that knowledge of the history of paradigms is necessary to make appropriate methodological choices in relation to the researcher’s own position within the contending paradigms. Some suggestions are offered for the way ahead that involve transdisciplinary approaches rather than modular epistemological separations.